The Anode Challenge for Lithium‐Ion Batteries: A Mechanochemically Synthesized Sn–Fe–C Composite Anode Surpasses Graphitic Carbon. Issue 4 (4th February 2016) - Dong, Zhixin; Zhang, Ruibo; Ji, Dongsheng; Chernova, Natasha A.; Karki, Khim; Sallis, Shawn; Piper, Louis; Whittingham, M. Stanley
Abstract : Carbon‐based anodes are the key limiting factor in increasing the volumetric capacity of lithium‐ion batteries. Tin‐based composites are one alternative approach. Nanosized Sn–Fe–C anode materials are mechanochemically synthesized by reducing SnO with Ti in the presence of carbon. The optimum synthesis conditions are found to be 1:0.25:10 for initial ratio of SnO, Ti, and graphite with a total grinding time of 8 h. This optimized composite shows excellent extended cycling at the C/10 rate, delivering a first charge capacity as high as 740 mAh g −1 and 60% of which still remained after 170 cycles. The calculated volumetric capacity significantly exceeds that of carbon. It also exhibits excellent rate capability, delivering volumetric capacity higher than 1.6 Ah cc −1 over 140 cycles at the 1 C rate. Abstract : An alternative lithium‐battery anode based on a tin–iron–carbon composite far surpasses the capacity of carbon for more than 100 charge–discharge cycles. It also has double the volumetric capacity of a graphite‐based anode, which will allow batteries that are either smaller or in the same size have longer lifetimes.